Resolução Temporal, localização e identificação de sons verbais degradados em portadores de perda auditiva unilateral com e sem dificuldade de linguagem - Nishihata, Regiane [UNIFESP] (2010)
The goal of this research is to verify the temporal resolution , sound localization and identification of degraded verbal sounds in individuals with unilateral hearing loss and investigate possible associations with learning or language disorders. Method: Twenty-six 8 to 15 year-old girls and boys participated in this study .Thirteen had normal hearing ( GSP ).Thirteen had a unilateral hearing loss ( GP ) and were divided into 2 groups: GPAD, with right hearing loss, and GPAE, with left hearing loss . An anamnesis was performed with parents who provided information about child’s auditory, communicative and linguistic behavior as well as performance at school. They informed what the risk factors were, the age of the child when they suspected there might be a hearing loss and the age when the diagnosis was established .The individuals underwent auditory processing assessment with speech in noise tests, sound localization and a gap detection test (RGDT).The data were analyzed with non- parametric tests and a 0.05 significance level. Results. There was no significant difference between the group with hearing loss (GP) and the group without hearing loss (GSP) as to temporal resolution. There was significant difference between the group with hearing loss (GP) and the group without loss (GSP) in degraded sound analysis through speech in noise test. There was significant difference between the group with hearing loss (GP) and the group without loss (GSP) in sound localization in five directions. The group with hearing loss (GP) presented more auditory, communicative and linguistic difficulties than the group without hearing loss. Within the group with hearing loss (GP), the children with right hearing loss ( GPAD ) had a history of speech and language delay, failed at school, attended school remedial programmes , and had behavioural problems more often than GPAE, the children with left hearing loss . Conclusion: Temporal resolution did not distinguish individuals without hearing loss and those with unilateral hearing loss. Individuals with unilateral hearing loss did less well in sound localization and closure tasks and did not communicate as proficiently as those without hearing loss. The Individuals with right hearing loss (GPAD) had often had speech and language delay, academic difficulty, and behavioural problems.